Governance and institutions - Mendoza, Ronald U (Archīum Ateneo, 2018)
Poor governance and weak public institutions can undermine even the most well-crafted policies to promote inclusive development. Corruption, poor public service delivery, misallocation of resources, political instability, uncoordinated government agencies and deeply embedded patron–client relationships are among the challenges of governance and institutions that slow down or defeat any socio-economic reform agenda. In particular, corruption is a sizable problem in the Philippines, affecting all sectors and levels of government. In this chapter we refer to governance as the manner in which public officials and institutions acquire and exercise the authority to facilitate collective action, craft public policy and provide public goods and services. On the other hand, institutions refers to the formal and informal rules that shape human interaction and their related enforcement mechanisms. Institutions therefore determine the possibilities for effective governance and collective action (see Figure 9.1). Both the government and market need institutions to function well. Otherwise, government and market failures are likely to litter the landscape instead of properly provided public goods and services. When government and markets work, then collective action outcomes—public goods and services—are more likely to succeed.